قيام الدولة الإسلامية المستدامة في شبه القارة الهندية وتطور العلوم والفنون؛ دراسة نقدية: THE ESTABLISHMENT OF SUSTAINABLE ISLAMIC GOVERNANCE IN THE INDIAN SUBCONTINENT AND THE EVOLUTION OF SCIENCES AND ARTS: A CRITICAL STUDY - Dr Hafiz Ahmed Saeed Rana; Muhammad Sohail (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
This paper provides a critical historical overview of the emergence and consolidation of Islamic governance in the Sind region, focusing on the intricate relationship between political authority and scholarly activities during various periods. It examines the period when the Caliphate’s central authority struggled to maintain control over distant territories like Sind, which often served as a battleground for internal tribal conflicts. Despite the deployment of governors from the Caliphate, such as Haroon ibn Abi Khalid Al-Marwazi, local governance under figures like Omar bin Abdul Aziz Al-Hibarari gained a degree of autonomy strong enough to challenge the Caliphate’s direct influence. The study traces the establishment of the first independent Islamic state in the region under Al-Hibarari’s leadership, highlighting how his rule paved the way for significant advancements in administration, the sciences, and arts. This period also saw the proliferation of Islamic scholarship, with the region becoming a fertile ground for intellectual and theological discourse. Key historical texts by scholars like Al-Ya’qubi and Al-Masudi provide insights into the governance practices and cultural contributions of these early Islamic rulers in Sind. Furthermore, the paper discusses the shifts in religious and scholarly orientations over time, with particular attention to the transition from Sunni to Shia (specifically Ismaili) dominance under different rulers. This change significantly influenced the theological and educational landscape of the region, contributing to a diverse scholarly tradition that encompassed various Islamic sects and schools of thought. The establishment of educational institutions and the role of prominent scholars in promoting Islamic sciences, including jurisprudence and theology, are also examined. This analysis underscores the interconnectedness of political stability and intellectual vitality, illustrating how governance in Sind evolved in tandem with scholarly endeavors that helped disseminate and entrench Islamic teachings in the Indian subcontinent. The paper concludes by reflecting on the enduring impact of these developments on the regional history of Islam and its scholarship.